ORGANIZATION OF PROTECTED ACCESS TO WEB SERVERS BY MEANS OF MACHINE LEARNING - Коробейнікова, Тетяна; Кравчук, Назар (SWorldJournal, 2023)
The article explores the increasing security threat in the global cyberspace. Measures for assessing information access risks considering individuals’ responsibility are proposed. Special attention is given to safeguarding web servers from CSRF attacks a